Liquidity provision in transition economy: the lessons from Russia - Anna Dorbec (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
This paper provides micro and macroeconomic analysis of the economic role of banks in the Russian economy.Using a large panel containing Russian enterprises' balance sheet and income statement data, we evaluate the determinants of bank financing.Econometric model put out the existence of liquidity providing activity of Russian banks.Even though the overall liquidity provision system suffers from certain deficiencies, we demonstrate its importance in the macroeconomic context, using time series econometric analysis. Bank credit appears to be a significant factor in explaining the non-payment dynamics and use of informal financing.Finally, the uncertainty concept helps us to understand the reasons for a limitation of Russian banks in their liquidity providing role.
URN:NBN:fi:bof-201408072100
Keywords: D80; G21; 330; liquidity; finance; transition; Russia; uncertainty; banks; inter-enterprise credit